Provocation: Business schools and economic crisis – a need for a rethink?. (1st February 2010) - Haynes, Michael
This paper reviews the main elements of the development of the financial and economic crisis from 2007/8. It considers the extent to which the teaching of business schools contributed to this in terms of misleading approaches to the issue of managers, leadership, human resource development research methods and so on. It argues that business school teaching has been too much for business rather than about it and that critical management studies has come to share this narrower focus.